y=[(x+2)*√(1-x²)]/[4x³] i got as far as y'/y=ln(x+2)+1/2ln(1-x²)-3ln4x im not sure if the part is correct since the cubed is only on the x and not the 4.
Follow Math Help Forum on Facebook and Google+
Originally Posted by johnnyc418 y=[(x+2)*√(1-x²)]/[4x³] i got as far as y'/y=ln(x+2)+1/2ln(1-x²)-3ln4x im not sure if the part is correct since the cubed is only on the x and not the 4. note that can be simplified to
alright so knowing that, would the answer be y'=([(x+2)*√(1-x²)]/[4x³])*([1/x+2]-[x/1-x²]-3/x] or is there any simplifying i could do it it. thanks
Originally Posted by johnnyc418 alright so knowing that, would the answer be y'=([(x+2)*√(1-x²)]/[4x³])*([1/x+2]-[x/1-x²]-3/x] or is there any simplifying i could do it it. thanks Indeed it would be, you might be able to work on it but I wouldn't bother
View Tag Cloud